2006 IEEE/RSJ International Conference on Intelligent Robots and Systems 2006
DOI: 10.1109/iros.2006.282185
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity in the Evaluation of the Impression of Robot Bodily Expressions

Abstract: Controlling devices using physiological signals is an increasingly active research field in human-robot interaction. Using brain signals, or Electroencephalograms (EEG), to control devices is widely known as Brain-Computer Interfacing (BCI). In a BCI system, brain signals are used to directly control devices and not as a communication channel, so target applications are restricted to handicapped and aged people. On the other hand, it is possible for healthy people to simply control devices using voice and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Research in cognitive neuroscience has shown that the power of low-alpha frequency band is the most reactive band to social cues such as movements (Allison et al, 2000;Cochin et al, 1998). We suppose that this frequency band reacts in a similar way to robot bodily expressions (Khiat et al, 2006). The next step in assessing the impression is to observe the amount of change in the power of low-alpha frequency band compared to the whole spectrum.…”
Section: Assessment Of Impression and Expressiveness Of Bodily Expresmentioning
confidence: 99%
“…Research in cognitive neuroscience has shown that the power of low-alpha frequency band is the most reactive band to social cues such as movements (Allison et al, 2000;Cochin et al, 1998). We suppose that this frequency band reacts in a similar way to robot bodily expressions (Khiat et al, 2006). The next step in assessing the impression is to observe the amount of change in the power of low-alpha frequency band compared to the whole spectrum.…”
Section: Assessment Of Impression and Expressiveness Of Bodily Expresmentioning
confidence: 99%